THE EFFECTIVENESS OF THE USE OF STRIKES BASED ON THE ANALYSIS OF COMPETITIVE ACTIVITY STUDENTS OF RUS "GTSOLIFK" IN TAEKWONDO WTF AT THE MOSCOW 2023 CHAMPIONSHIP - Epov O.G.; Sirotkina Y.A.; Chekanova E.P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the effectiveness of the use of strikes based on the analysis of the competitive activity of students of RUS "GTSOLIFK" in taekwondo WTF at the Moscow Championship 2023. Methods and structure of the study. To assess the technical actions, a video analysis of 13 competitive matches of the 2023 Moscow Championship was conducted. To assess the number of strikes, a video analysis of competitive duels was conducted. The final number of blows for the duel was made up of: single blows, blows performed in fencing, as well as from blows that consisted in a series. Results and conclusions. As a result of video analysis of competitive duels, the percentage of strikes performed during the duel was revealed. The most frequently performed blow is dolio-chagi with the near leg to the body (30.4%); the most effective blows are: hurio-chagi to the head (0.167%) and a hand blow (0.148%). It was also revealed that men strike more blows per round and are 2 times more effective than women.